2018
DOI: 10.1021/acschemneuro.8b00337
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Chemical Determinants of BL-1249 Action and Selectivity for K2P Channels

Abstract: K potassium channels generate leak currents that stabilize the resting membrane potential of excitable cells. Various K channels are implicated in pain, ischemia, depression, migraine, and anesthetic responses, making this family an attractive target for small molecule modulator development efforts. BL-1249, a compound from the fenamate class of nonsteroidal anti-inflammatory drugs is known to activate K2.1(TREK-1), the founding member of the thermo- and mechanosensitive TREK subfamily; however, its mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 61 publications
8
42
0
Order By: Relevance
“…Consistent with the deletion of key ML335 binding SF2-M4 loop residues, Loop2Sym-6 was unresponsive to ML335 ( Fig. 4 i,j), but remained partially sensitive to BL-1249, an activator that affects the channel from a site under the selectivity filter 33,34 . Importantly, measurement of rectification in inside-out patches, a parameter that is a direct measure of C-type gate activation 5,7 , demonstrated that unlike gain-of-function mutants 7 , Loop2Sym-6 does not have a constitutively activated C-type gate that would render it insensitive to gating commands ( Fig.…”
supporting
confidence: 63%
“…Consistent with the deletion of key ML335 binding SF2-M4 loop residues, Loop2Sym-6 was unresponsive to ML335 ( Fig. 4 i,j), but remained partially sensitive to BL-1249, an activator that affects the channel from a site under the selectivity filter 33,34 . Importantly, measurement of rectification in inside-out patches, a parameter that is a direct measure of C-type gate activation 5,7 , demonstrated that unlike gain-of-function mutants 7 , Loop2Sym-6 does not have a constitutively activated C-type gate that would render it insensitive to gating commands ( Fig.…”
supporting
confidence: 63%
“…35 The rationale for the earlier experiments, was because of the high sequence dissimilarity between rodent TASK-1 and TASK-3 C-termini. 37,38 Surprisingly, however, truncation of murTASK-3 channels, resulted in a significant reduction in current recorded through these channels, but this still attenuated the effect of doxapram. Because of the importance of this region for signalling inputs, such as phosphorylation, 36 one can hypothesize that the phosphorylation state of the channel may be important for doxapram's effect, particularly as the number of putative phosphorylation sites are different between TASK-1 and TASK-3, with more predicted sites on mouse and human TASK-3.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, for known gain-of-function mutations on these channels and other related K2P channels, regulation by blockers or activators is modified when the link between the C-terminus and the selectivity filter is disrupted. 37,38 Surprisingly, however, truncation of murTASK-3 channels, resulted in a significant reduction in current recorded through these channels, but this still attenuated the effect of doxapram. With the structure of the intracellular C-termini of K2P channels not determined by existing crystal structures, the involvement of this region remains difficult to evaluate.…”
Section: Discussionmentioning
confidence: 98%
“…During the review of the present paper, several novel and important results were published by Schewe and coworkers, contrasting the proposed classification presented earlier and other previous results (Schewe et al., ). BL‐1249 was revealed as a polypharmacological activator, acting on multiple K2P channels, including THIK‐1, providing partially different results than the ones obtained in previous papers (Lolicato et al., ; Pope et al., ), and suggesting that experimental procedures can influence the results and have to be taken with caution. Electron maps of TREK‐2 complexed with a brominated derivative of BL‐1249 revealed bromine peak densities near the side fenestrations, suggesting the ligand positions near or in the fenestrations and favors increased K + ion occupancy under the SF through its tetrazolic negative charge, thus increasing ion permeation rate through the SF.…”
Section: Trek Subfamily Channels and Their Interactions With Modulatomentioning
confidence: 70%
“…However, it is noteworthy how mutation Q258K in TRAAK leads to some improvements to its response to small concentrations of BL‐1249 and even of ML67‐33 (Supplemental figure 7K in Lolicato et al. ), which should be investigated further, especially as BL‐1249 activates TRAAK only at high concentrations (Pope et al., ). Interestingly to note, activation resulted more readily by extracellular application of both ML67‐33 and BL‐1249 (Bagriantsev et al., ), a particular aspect that was also observed in testing GI‐530139, which activates TREK‐1 and TREK‐2 but not TRAAK (Loucif et al., ) and caffeic acid derivatives as TREK‐1 activators (Danthi, Enyeart, & Enyeart, ).…”
Section: Trek Subfamily Channels and Their Interactions With Modulatomentioning
confidence: 99%